2017
DOI: 10.1590/1413-785220172504158091
|View full text |Cite
|
Sign up to set email alerts
|

Associated Posterior Pelvic Injury Patterns in Transverse-Oriented Acetabular Fracture

Abstract: Objective: Our study analyzed the incidence of posterior pelvic injury patterns and their influence on the surgical treatment of transverse-oriented acetabular fractures . Methods:Fifty-one transverse-oriented acetabular fracture cases admitted between 1999 and 2013 were evaluated retrospectively. Comparative studies were performed for groups organized by acetabular fracture type, degree of sacroiliac separation, and postoperative reduction quality . Results: Associated posterior pelvic injuries were found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Simple transverse fractures are traditionally regarded as transverse-oriented acetabular fractures according to the common concomitant disruption of the pelvic ring [ 5 , 24 , 25 ]. However, there is no clear theorem to confirm the impact direction during the fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Simple transverse fractures are traditionally regarded as transverse-oriented acetabular fractures according to the common concomitant disruption of the pelvic ring [ 5 , 24 , 25 ]. However, there is no clear theorem to confirm the impact direction during the fracture.…”
Section: Discussionmentioning
confidence: 99%
“…For acetabular injury, six used the Judet and Letournel classification [ 1 , 3 , 10 - 13 ], one used AO/OTA classification for the acetabulum [ 2 ], one used both Judet and Letournel and AO/OTA classification for the acetabulum [ 7 ], and three did not provide specific classification [ 4 , 8 - 9 ]. When possible, acetabular fractures were reclassified from Judet and Letournel to AO/OTA classification of acetabulum [ 10 - 11 , 13 ]. Of the 985 patients, 450 patients had an average Injury Severity Score (ISS) of 22.98 [ 1 - 2 , 7 - 8 , 11 - 13 ] Average ISS was calculated by the multiplication of each article’s individual sum cases by their ISS, adding the individual sums of all seven studies and then dividing by the total sum of 450 patients to collect the average of seven studies.…”
Section: Reviewmentioning
confidence: 99%
“…After the application of our defined eligibility criteria, a total of 18 studies were identified [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. One study was removed from our collected data due to duplicate data and six were removed as they did not meet inclusion criteria.…”
Section: Figure 1: Flow Diagrammentioning
confidence: 99%
See 2 more Smart Citations